What is $(\dfrac{{\sec 18^\circ }}{{\sec 144^\circ }} + \dfrac{{{\text{cosec18}}^\circ }}{{{\text{cosec144}}^\circ }})$ equal to?
A) ${\text{sec18}}^\circ $
B) ${\text{cosec18}}^\circ $
C) ${\text{ - sec18}}^\circ $
D) ${\text{ - cosec18}}^\circ $
Answer
Verified
456.6k+ views
Hint: Here we can see secant and cosecant are the reciprocals of cosine and sine respectively. So we can replace them. Then we can replace the angle \[144\] by $180 - 36$. So we can apply equations of $\cos 2\theta $ and $\sin 2\theta $. Then solving using trigonometric relations we get the answer.
Formula used: For any angle $\theta $ we have the following trigonometric relations.
$\sec \theta = \dfrac{1}{{\cos \theta }}$ and ${\text{cosec}}\theta = \dfrac{1}{{\sin \theta }}$
$\cos (180 - \theta ) = - \cos \theta $ and $\sin (180 - \theta ) = \sin \theta $
$\cos 2\theta = {\cos ^2}\theta - {\sin ^2}\theta $
$\sin 2\theta = 2\sin \theta \cos \theta $
${\sin ^2}\theta + {\cos ^2}\theta = 1$
Complete step-by-step solution:
We have to find the value of $(\dfrac{{\sec 18^\circ }}{{\sec 144^\circ }} + \dfrac{{{\text{cosec18}}^\circ }}{{{\text{cosec144}}^\circ }})$.
Since $\sec \theta = \dfrac{1}{{\cos \theta }}$ and ${\text{cosec}}\theta = \dfrac{1}{{\sin \theta }}$, we can write
$\Rightarrow$$\dfrac{{\sec 18^\circ }}{{\sec 144^\circ }} + \dfrac{{{\text{cosec18}}^\circ }}{{{\text{cosec144}}^\circ }} = \dfrac{{\cos 144^\circ }}{{\cos 18^\circ }} + \dfrac{{{\text{sin144}}^\circ }}{{{\text{sin18}}^\circ }}$
We can replace \[144\] by $180 - 36$. So we have,
$\Rightarrow$$\dfrac{{\sec 18^\circ }}{{\sec 144^\circ }} + \dfrac{{{\text{cosec18}}^\circ }}{{{\text{cosec144}}^\circ }} = \dfrac{{\cos (180 - 36)^\circ }}{{\cos 18^\circ }} + \dfrac{{{\text{sin}}(180 - 36)^\circ }}{{{\text{sin18}}^\circ }}$
For angles less than ${90^ \circ }$, $180 - \theta $ belongs to the second quadrant.
In the second quadrant sine and cosine values are positive and all other values are negative.
We know $\cos (180 - \theta ) = - \cos \theta $ and $\sin (180 - \theta ) = \sin \theta $
So we get from the above equation,
$\Rightarrow$$\dfrac{{\sec 18^\circ }}{{\sec 144^\circ }} + \dfrac{{{\text{cosec18}}^\circ }}{{{\text{cosec144}}^\circ }} = - \dfrac{{\cos 36^\circ }}{{\cos 18^\circ }} + \dfrac{{{\text{sin}}36^\circ }}{{{\text{sin18}}^\circ }}$
Now we have the equations:
$\cos 2\theta = {\cos ^2}\theta - {\sin ^2}\theta $
$\sin 2\theta = 2\sin \theta \cos \theta $
Using these equations we can write,
$\Rightarrow$$\cos 36^\circ = {\cos ^2}18^\circ - {\sin ^2}18^\circ $
$\Rightarrow$$\sin 36^\circ = 2\sin 18^\circ \cos 18^\circ $
Substituting these in the above equation we have,
$\Rightarrow$$\dfrac{{\sec 18^\circ }}{{\sec 144^\circ }} + \dfrac{{{\text{cosec18}}^\circ }}{{{\text{cosec144}}^\circ }} = - (\dfrac{{{{\cos }^2}18^\circ - {{\sin }^2}18^\circ }}{{\cos 18^\circ }}) + \dfrac{{2\sin 18^\circ \cos 18^\circ }}{{{\text{sin18}}^\circ }}$
Cancelling $\sin 18^\circ $ from numerator and denominator on the second term of right hand side of the above equation,
We have,
$\Rightarrow$$\dfrac{{\sec 18^\circ }}{{\sec 144^\circ }} + \dfrac{{{\text{cosec18}}^\circ }}{{{\text{cosec144}}^\circ }} = \dfrac{{{{\sin }^2}18^\circ - {{\cos }^2}18^\circ }}{{\cos 18^\circ }} + 2\cos 18^\circ $
Simplifying the above equation we get,
$\Rightarrow$$\dfrac{{\sec 18^\circ }}{{\sec 144^\circ }} + \dfrac{{{\text{cosec18}}^\circ }}{{{\text{cosec144}}^\circ }} = \dfrac{{{{\sin }^2}18^\circ - {{\cos }^2}18^\circ + 2{{\cos }^2}18^\circ }}{{\cos 18^\circ }}$
$ \Rightarrow \dfrac{{\sec 18^\circ }}{{\sec 144^\circ }} + \dfrac{{{\text{cosec18}}^\circ }}{{{\text{cosec144}}^\circ }} = \dfrac{{{{\sin }^2}18^\circ + {{\cos }^2}18^\circ }}{{\cos 18^\circ }}$
Also we know that
$sin^2 \theta + cos^2 \theta =1$
Using this result in the above equation we get,
$\Rightarrow$$\dfrac{{\sec 18^\circ }}{{\sec 144^\circ }} + \dfrac{{{\text{cosec18}}^\circ }}{{{\text{cosec144}}^\circ }} = \dfrac{1}{{\cos 18^\circ }}$
$\sec \theta = \dfrac{1}{{\cos \theta }} $
$\Rightarrow$$\dfrac{{\sec 18^\circ }}{{\sec 144^\circ }} + \dfrac{{{\text{cosec18}}^\circ }}{{{\text{cosec144}}^\circ }} = \sec 18^\circ $
Thus we get the solution.
$\therefore $ The answer is option A.
Note: We changed the trigonometric ratios to \[\sin \] and $\cos $ so that we can simplify easily. There are different trigonometric rules to solve these types of problems. We have to choose the appropriate equations in each step. For $\cos 2\theta $ we have four equations. But here we chose this one so that we can simplify the answer.
Formula used: For any angle $\theta $ we have the following trigonometric relations.
$\sec \theta = \dfrac{1}{{\cos \theta }}$ and ${\text{cosec}}\theta = \dfrac{1}{{\sin \theta }}$
$\cos (180 - \theta ) = - \cos \theta $ and $\sin (180 - \theta ) = \sin \theta $
$\cos 2\theta = {\cos ^2}\theta - {\sin ^2}\theta $
$\sin 2\theta = 2\sin \theta \cos \theta $
${\sin ^2}\theta + {\cos ^2}\theta = 1$
Complete step-by-step solution:
We have to find the value of $(\dfrac{{\sec 18^\circ }}{{\sec 144^\circ }} + \dfrac{{{\text{cosec18}}^\circ }}{{{\text{cosec144}}^\circ }})$.
Since $\sec \theta = \dfrac{1}{{\cos \theta }}$ and ${\text{cosec}}\theta = \dfrac{1}{{\sin \theta }}$, we can write
$\Rightarrow$$\dfrac{{\sec 18^\circ }}{{\sec 144^\circ }} + \dfrac{{{\text{cosec18}}^\circ }}{{{\text{cosec144}}^\circ }} = \dfrac{{\cos 144^\circ }}{{\cos 18^\circ }} + \dfrac{{{\text{sin144}}^\circ }}{{{\text{sin18}}^\circ }}$
We can replace \[144\] by $180 - 36$. So we have,
$\Rightarrow$$\dfrac{{\sec 18^\circ }}{{\sec 144^\circ }} + \dfrac{{{\text{cosec18}}^\circ }}{{{\text{cosec144}}^\circ }} = \dfrac{{\cos (180 - 36)^\circ }}{{\cos 18^\circ }} + \dfrac{{{\text{sin}}(180 - 36)^\circ }}{{{\text{sin18}}^\circ }}$
For angles less than ${90^ \circ }$, $180 - \theta $ belongs to the second quadrant.
In the second quadrant sine and cosine values are positive and all other values are negative.
We know $\cos (180 - \theta ) = - \cos \theta $ and $\sin (180 - \theta ) = \sin \theta $
So we get from the above equation,
$\Rightarrow$$\dfrac{{\sec 18^\circ }}{{\sec 144^\circ }} + \dfrac{{{\text{cosec18}}^\circ }}{{{\text{cosec144}}^\circ }} = - \dfrac{{\cos 36^\circ }}{{\cos 18^\circ }} + \dfrac{{{\text{sin}}36^\circ }}{{{\text{sin18}}^\circ }}$
Now we have the equations:
$\cos 2\theta = {\cos ^2}\theta - {\sin ^2}\theta $
$\sin 2\theta = 2\sin \theta \cos \theta $
Using these equations we can write,
$\Rightarrow$$\cos 36^\circ = {\cos ^2}18^\circ - {\sin ^2}18^\circ $
$\Rightarrow$$\sin 36^\circ = 2\sin 18^\circ \cos 18^\circ $
Substituting these in the above equation we have,
$\Rightarrow$$\dfrac{{\sec 18^\circ }}{{\sec 144^\circ }} + \dfrac{{{\text{cosec18}}^\circ }}{{{\text{cosec144}}^\circ }} = - (\dfrac{{{{\cos }^2}18^\circ - {{\sin }^2}18^\circ }}{{\cos 18^\circ }}) + \dfrac{{2\sin 18^\circ \cos 18^\circ }}{{{\text{sin18}}^\circ }}$
Cancelling $\sin 18^\circ $ from numerator and denominator on the second term of right hand side of the above equation,
We have,
$\Rightarrow$$\dfrac{{\sec 18^\circ }}{{\sec 144^\circ }} + \dfrac{{{\text{cosec18}}^\circ }}{{{\text{cosec144}}^\circ }} = \dfrac{{{{\sin }^2}18^\circ - {{\cos }^2}18^\circ }}{{\cos 18^\circ }} + 2\cos 18^\circ $
Simplifying the above equation we get,
$\Rightarrow$$\dfrac{{\sec 18^\circ }}{{\sec 144^\circ }} + \dfrac{{{\text{cosec18}}^\circ }}{{{\text{cosec144}}^\circ }} = \dfrac{{{{\sin }^2}18^\circ - {{\cos }^2}18^\circ + 2{{\cos }^2}18^\circ }}{{\cos 18^\circ }}$
$ \Rightarrow \dfrac{{\sec 18^\circ }}{{\sec 144^\circ }} + \dfrac{{{\text{cosec18}}^\circ }}{{{\text{cosec144}}^\circ }} = \dfrac{{{{\sin }^2}18^\circ + {{\cos }^2}18^\circ }}{{\cos 18^\circ }}$
Also we know that
$sin^2 \theta + cos^2 \theta =1$
Using this result in the above equation we get,
$\Rightarrow$$\dfrac{{\sec 18^\circ }}{{\sec 144^\circ }} + \dfrac{{{\text{cosec18}}^\circ }}{{{\text{cosec144}}^\circ }} = \dfrac{1}{{\cos 18^\circ }}$
$\sec \theta = \dfrac{1}{{\cos \theta }} $
$\Rightarrow$$\dfrac{{\sec 18^\circ }}{{\sec 144^\circ }} + \dfrac{{{\text{cosec18}}^\circ }}{{{\text{cosec144}}^\circ }} = \sec 18^\circ $
Thus we get the solution.
$\therefore $ The answer is option A.
Note: We changed the trigonometric ratios to \[\sin \] and $\cos $ so that we can simplify easily. There are different trigonometric rules to solve these types of problems. We have to choose the appropriate equations in each step. For $\cos 2\theta $ we have four equations. But here we chose this one so that we can simplify the answer.
Recently Updated Pages
Master Class 12 Business Studies: Engaging Questions & Answers for Success
Master Class 12 English: Engaging Questions & Answers for Success
Master Class 12 Social Science: Engaging Questions & Answers for Success
Master Class 12 Chemistry: Engaging Questions & Answers for Success
Class 12 Question and Answer - Your Ultimate Solutions Guide
Master Class 12 Economics: Engaging Questions & Answers for Success
Trending doubts
Which are the Top 10 Largest Countries of the World?
Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE
What are the major means of transport Explain each class 12 social science CBSE
What is the Full Form of PVC, PET, HDPE, LDPE, PP and PS ?
What is a transformer Explain the principle construction class 12 physics CBSE
Explain sex determination in humans with the help of class 12 biology CBSE